PENGARUH ATRIBUT PRODUK DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN KARTU SELULER SIMPATI PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Rutmana Silalahi; Gusnardi '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research is done to University of Riau Economic Education students to examine about the effect of product attribute and brand image on customer satisfaction of sympathetic cellular card. Sampling with proportional random sampling. While the data analysis technique used in this research is Multiple Linear Regression Analysis (f test and t test). Based on result of analysis of test data f, that product attribute and brand image together have significant effect to satisfaction. Based on t test, product attribute have an effect on to customer satisfaction 2,171 is significant, on brand image to customer satisfaction have influence equal to 7.024 is significant. If the attribute of the product and the brand image of the sympathy card is very good and can meet the customer's needs, the company succeeded in achieving the sympathetic cellular subscriber's satisfaction, but if the product attribute and the brand image of the sympathetic mobile card is not good then the company fails to give satisfaction to the customer because the company does not menyedikan According to customer requirement of cellular card usage.Keywords: Product Attributes, Brand Image, Customer Satisfaction.